2019
DOI: 10.1021/acs.macromol.9b00922
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Long-Spaced Precision Polyacetals I: Melting and Recrystallization of Rapidly Formed Crystallites

Abstract: Rapidly melt-crystallized polyethylenes with acetal groups (−O–CH2–O−) precisely spaced by 12, 18, 19, or 23 methylene backbone carbons exhibit two reorganizations and three melting endotherms on heating at relatively low heating rates. Real-time wide-angle X-ray diffraction (WAXD) experiments further confirm that these transitions are associated with a reorganization to a different crystalline structure. The differential scanning calorimetry endotherms are associated with melting of the initially formed disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(77 citation statements)
references
References 76 publications
7
70
0
Order By: Relevance
“…Prior works demonstrated that crystallites of polyacetals are layered, in other words, two or more polyacetal repeating units participate in the crystallite with inter-chain staggering of the acetal groups (-O–CH 2 –O-) in planes that are about normal to the chain axis [ 8 ]. The number of layers in the crystal increases with increasing acetal content in the chain [ 8 , 9 ]. Since the melting point and heat of fusion decrease also proportionally to the increasing content of acetal, the trends of Figure 1 c,d reflect the role of the acetal group as a defect in the crystal, restricting crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior works demonstrated that crystallites of polyacetals are layered, in other words, two or more polyacetal repeating units participate in the crystallite with inter-chain staggering of the acetal groups (-O–CH 2 –O-) in planes that are about normal to the chain axis [ 8 ]. The number of layers in the crystal increases with increasing acetal content in the chain [ 8 , 9 ]. Since the melting point and heat of fusion decrease also proportionally to the increasing content of acetal, the trends of Figure 1 c,d reflect the role of the acetal group as a defect in the crystal, restricting crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Corrected SAXS intensities ( I ( q )) were used to obtain the normalized one-dimensional correlation function of the electron density fluctuations normal to the lamellar stacks according to [ 16 , 17 ], where q is the scattering angle, and r the correlation length. The long period ( L ) and crystal thickness ( l c ) were obtained as described in prior works [ 8 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyacetals deviate from this picture in that accommodation in the crystals is hindered due to the conformations of acetal groups not being compatible with an all-trans arranged methylene chain. [28,30] [22]. Published by the Royal Society.…”
Section: Methodsmentioning
confidence: 99%